APPLICATION OF TRAP BARRIER SYSTEM COMBINED WITH CAGE TRAP FOR CONTROLLING RATS IN RICE FIELD - Sekarweni, Hastin Wulan; Pujiastuti, Yulia; Herlinda, Siti (BIOVALENTIA: Biological Research Journal, 2019)
Rice-field rat is a main pest of rice. Yield reduction caused by rat is quite high, because rats attack rice plant at all stages. One of the efforts applied to control rats is by using Trap Barrier System combined with cage trap. The objective of this research was to identify species of rat attacking rice plants and investigate the presence of  rat by their footprints. The experiment was conducted in Jalur 6  Village Sumber Mulya, Sub-district  Muara Telang,  District Banyuasin, South  Sumatra. One hectare of farmer’s rice field, divided into 3 sub-plot. Each sub-plot was planted with variety paddy of Inpari 22 (sub-plot A), Inpari 33 (sub-plot B), and Inpari 43 (sub-plot C). The number of cage traps was 6 traps per sub-plot. Observations were made 7 times, with an interval of 10 days. Results showed species of trapped rats in the research area was Rattus argentiventer, in which number of males was higher than females. Morphologically, the size of males were bigger than female. Number of footprints did not reperesentative the number of trapped rats. Inpari 43 variety was more preferred by rats because damage intensity was the highest than other two rice varieties.